2016
DOI: 10.1111/pce.12832
|View full text |Cite
|
Sign up to set email alerts
|

Non‐selective cation channel activity of aquaporin AtPIP2;1 regulated by Ca2+ and pH

Abstract: The aquaporin AtPIP2;1 is an abundant plasma membrane intrinsic protein in Arabidopsis thaliana that is implicated in stomatal closure, and is highly expressed in plasma membranes of root epidermal cells. When expressed in Xenopus laevis oocytes, AtPIP2;1 increased water permeability and induced a non-selective cation conductance mainly associated with Na . A mutation in the water pore, G103W, prevented both the ionic conductance and water permeability of PIP2;1. Co-expression of AtPIP2;1 with AtPIP1;2 increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
179
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(188 citation statements)
references
References 59 publications
(73 reference statements)
7
179
0
2
Order By: Relevance
“…We hypothesize that in stem tissues SvPIP2;1 is involved in cell growth and that SvNIP2;2 may facilitate water movement and potentially the flow of other solutes into the apoplasm to sustain solute transportation by bulk-flow, and possibly ‘recycle’ water used for solute delivery back to the xylem. It is expected that SvPIP2;1 could have additional roles, as other PIP water channels have been shown to also be permeable to CO 2 , hydrogen peroxide, urea, sodium and arsenic (Siefritz et al, 2001; Uehlein et al, 2003; Mosa et al, 2012; Bienert and Chaumont, 2014; Byrt et al, 2016b). SvNIP2;2 could have roles such as transporting neutral solutes to the apoplasm, as previous studies report silicic acid, urea, and boric acid permeability for other NIPS (Bienert et al, 2008; Ma et al, 2008; Ma and Yamaji, 2008; Li et al, 2009; Deshmukh et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesize that in stem tissues SvPIP2;1 is involved in cell growth and that SvNIP2;2 may facilitate water movement and potentially the flow of other solutes into the apoplasm to sustain solute transportation by bulk-flow, and possibly ‘recycle’ water used for solute delivery back to the xylem. It is expected that SvPIP2;1 could have additional roles, as other PIP water channels have been shown to also be permeable to CO 2 , hydrogen peroxide, urea, sodium and arsenic (Siefritz et al, 2001; Uehlein et al, 2003; Mosa et al, 2012; Bienert and Chaumont, 2014; Byrt et al, 2016b). SvNIP2;2 could have roles such as transporting neutral solutes to the apoplasm, as previous studies report silicic acid, urea, and boric acid permeability for other NIPS (Bienert et al, 2008; Ma et al, 2008; Ma and Yamaji, 2008; Li et al, 2009; Deshmukh et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…It has been widely accepted that members of the AQP family, including those from the NIP subfamily, transport noncharged molecules (25,26), although recent studies have suggested that some members of the AQP family could transport charged substrates (27,28). However, the major Al species at low pH (4.2) is the charged Al 3+ ion (29).…”
Section: Nip1;2 Facilitates Passive Bidirectional Aluminum Transport mentioning
confidence: 98%
“…Also, there is mounting evidence that aquaporins are also implicated in Na + uptake in plants (Byrt et al, 2017). The Na + absorbed by the root then moves to the xylem with the aid of other transporters and channels and is delivered to the shoot, especially the leaf blade, where its effects are most felt (Munns and Tester, 2008).…”
Section: Sodium Homeostasismentioning
confidence: 99%
“…In animals, some aquaporins also mediate ion transport (Ikeda et al, 2002), which prompted investigation of possible similar roles in plants. It was not until recently that such a role was shown to be indeed present in plants, at least in Arabidopsis (Byrt et al, 2017) where the phenomenon was evaluated. In this study, electrophysiological studies using Xenopus oocytes and yeast complementation tests showed that Arabidopsis thaliana plasma membrane intrinsic protein AtPIP2;1 has strong Na + conductance, although it was not clear from the study whether it is Na + -selective or not.…”
Section: Mechanisms Restricting Na+ Uptake Determine Tolerance To Salmentioning
confidence: 99%